Exploring the Biocontrol Potential of Fungus Alternaria gaisen GD-011 in the Tibetan Plateau - Haixia Zhu; Huan Li; Yongqiang Ma (Plants, 2025)
In screening for biocontrol strains with broad-spectrum and efficient herbicidal activity, strain GD-011 isolated from naturally susceptible M. sativa (Medicago sativa L.) roots was selected as a promising candidate. The control effects of strain GD-011 on nine weeds of Qinghai farmland were evaluated in vitro and in vivo, and its safety to five local crops was tested. The in vivo spray inoculation test showed that strain GD-011 had a strong pathogenic effect on the weeds M. verticillata (Malva verticillata L.), E. densa (Elsholtzia densa Benth), and A. fatua (Avena fatua L.), with incidence rates of more than 80.87% and fresh weight control effects of more than 71.8%. Crop safety tests showed that the B. napus (Brassica napus L.) crop is moderately susceptible to strain GD-011, with slight reactions in H. vulgare (Hordeum vulgare L.), but strain GD-011 is safe for T. aestivum (Triticum aestivum L.), P. sativum (Pisum sativum L.), and V. faba (Vicia faba L.) Observations on the morphological characteristics combined with a sequence analysis of the ribose rDNA internal transcribed spacer (rDNA ITS), the Elongation factor (EF-1α) gene, and the antigen-related protein gene (Alt a1) identified strain GD-011 as Alternaria gaisen. Scanning electron microscopy observations showed that the mycelia of strain GD-011 invaded the leaf tissue through the stomata on the surface, with the formation of a parasitic mycelium network on the surface of the tissue, the metabolism of E. densa leaf tissues was disturbed, and leaf tissues appeared to be broken. From the perspective of its herbicidal potential, the metabolites of strain GD-011 have good control effects on most weeds and are relatively safe for crops.